Regulation of CD4+ and CD8+ T Cell Responses by Extract of Male Papaya Leaves (Carica papaya L.) in Experimental Autoimmune Disease - Lisa Savitri; Kharisul Ihsan; Elfred Rinaldo Kasimo; Rochmad Krissanjaya (Biology, Medicine, & Natural Product Chemistry, 2026)
Autoimmune diseases are characterized by dysregulated adaptive immune responses, particularly involving CD4+ and CD8+ T lymphocytes. Current therapeutic strategies often rely on broad immunosuppression, which may lead to adverse effects and increased susceptibility to infections. Therefore, the exploration of natural immunomodulatory agents remains an important research focus. This study aimed to evaluate the regulatory effects of male papaya leaf extract (Carica papaya L.) on CD4+ and CD8+ T cell responses in an experimental autoimmune disease model. Male papaya leaves were extracted using 70% ethanol and administered orally to autoimmune disease-induced mice at different dosage levels. T cell populations were analyzed using flow cytometry, focusing on CD4+ and CD8+ T cell proportions in splenocytes. The results showed that experimental autoimmune disease significantly increased CD4+ T cell levels and reduced CD8? T cell proportions compared to normal controls. Treatment with male papaya leaf extract led to a dose-dependent reduction in CD4+ T cells and restoration of CD8+ T cell levels. The highest dose produced a T cell profile comparable to that of healthy animals. These findings indicate that male papaya leaf extract modulates adaptive immune responses by rebalancing CD4+ and CD8+ T cell populations rather than inducing broad immunosuppression. The study highlights the potential of male papaya leaf extract as a natural immunomodulatory agent for the management of autoimmune diseases and supports further investigation into its underlying mechanisms and clinical relevance.